Pattern of Big Data Application for Development to Smart Factory - Ingkapradit, Chinnaphat; Deelers, Sirichai (Business Administration and Management Journal Review, 2021)
An objective of this research is to study big data applications, results and success factors from manufacturers that being developed to smart factory in Thailand. This is qualitative research with case study research method. The key informants are 4-manufacturers that applied big data. The finding reveals 7 categories of big data application such as process monitoring, parameter optimization, quality improvement, predictive maintenance, material tracking, energy management and employee tracking. Big data results in improvement of performance matric in 3-categories: cost such as overall equipment efficiency, loss reduction and energy efficiency, quality such as defect rate and customer complaint and time for on-time delivery rate. Success factors of big data are organization-oriented factor, system-oriented factor, resource-oriented factor and data-oriented factor which big data development is focused on bottleneck processes that required to improve their performance.